Future of clay-based construction materials – A review. (20th June 2019) - Shubbar, Ali Abdulhussein; Sadique, Monower; Kot, Patryk; Atherton, William
Highlights: A range of methods were reviewed in the production of clay-based building materials. Microwave heating significantly reduced sintering, curing and drying time. More research on environmental and economic aspects of clay-based building materials is needed. Abstract: Sustainability in the manufacture of different construction materials raises many important issues. Nowadays, there is increasing demand for such materials to be produced using environmentally friendly, low energy consuming production methods. This paper presents a review of the current research relating to the use of various production techniques for clay-based construction materials. The techniques which will be reviewed are: blending and stabilising, alkali activation (geopolymerisation) and the use of microwave heating as an innovative sintering, curing and drying method. The advantages and disadvantages of each technique will be discussed. Additionally, a comparison between the environmental and economic aspects of the studied production techniques along with some suggestions to improve the sustainability of different production techniques will be discussed.